(untitled) (Papeles, 2026)
Introduction: Learning about the experiences of university students is a valuable source of feedback for everyone involved, from the students to the institutions where they are educated. The objective of this research allowed to describe the experiences of students of a degree in education in virtual modality, obtained during their professional internships in the design and implementation of an educational project, through virtual platforms in the rural community of Yaxchekú, Yucatán, Mexico. Methodology: The approach was qualitative. The content analysis technique was used on the final reports submitted by university students after their professional practices were concluded. Results and discussions: It was found that the experiences of university students were significant in terms of the usefulness of the design and implementation of the activities that shaped the educational project; the relevance of the educational project in the acquisition of relevant experiences; the opportunity to reflect on professional practices, as well as in the establishment of conclusions regarding achievements and opportunities for improvement. Conclusion: The experiences expressed are a valuable comment of feedback, not only for the educational project but for the academic program they are studying.